The reality of the physical and Moral Environment of public schools in the University Brigade Directorate in the Jordanian Capital Amman - omari, Nihima mohammed amin (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the reality of school environment, both material and moral in public schools in Al-Jam’a Directorate of Education in the Jordanian capital Amman, from the teachers’ point of view. The study uses the descriptive survey method, and the tool consists of a questionnaire of (30) items, which were distributed to a sample of (400) male and female teachers: (155) males, and (245) females. They are distributed among (13) schools in the University District Directorate, and by using the statistical program (SPSS), the study found the following: That the general physical and moral environment of public schools in the University District Directorate obtained an overall average (2.25 out of 4) with a grade of (average) and at the level of both fields The two presidents; The moral environment reality got a medium (2.26). And the physical environment got a medium of (2.24), and both of them got a rating of (average). The results also showed the existence of statistically significant differences between the sexes, in the reality of the moral environment in favor of females. In light of these results, the researcher presented a number of recommendations and proposals to improve the physical and moral school environment. In the University District Directorate and the whole Kingdom of Jordan.